The philosophy of law : an encyclopedia - Gray, Christopher B. (Garland reference library of the humanities, 2012)
From articles centering on the detailed and doctrinal exposition of the law to those which reside almost wholly within the realm of philosophical ethics, this volume affords comprehensive treatment to both sides of the philosophico-legal equation. Systematic and sustained coverage of the many dimensions of legal thought gives ample expression to the true breadth and depth of the philosophy of law, with coverage of: The modes of knowing and the kinds of normativity used in the law; Studies in international, constitutional, criminal, administrative, persons and property, contracts and to.